Determination of the optimal mode of FDM printing with composites to obtain the required design and technological parameters - I. D. Markanov; R. A. Vdovin; E. S. Goncharov; A. O. Firsin (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
This paper discusses properties of various 3D printing materials, namely, plastics, including polyamides, along with composite or engineering plastics with inclusions of carbon fiber and fiberglass. We have selected an optimal sample printing mode and carried out experiments, following which we have determined maximal loads for test composite materials, and linear shrinkage. As the result, we have determined an optimal 3D printing mode for various structures of composite material parts with the purpose to reach the set design–engineering parameters.